Resistance Analysis Of Purse Seine Ship Due To Redesign Of Fish Hold In Consideration Of Local Wisdom In Sinjai Regency (Journal of Pharmaceutical Negative Results, 2023)
carrying out fishing operations. The design of traditional fishing boats with a scientific approach to the hydrodynamic aspects of vessel resistance is carried out in order to ensure the safety of traditional fishing boats. Resistance information will be used as a reference for determining the main and auxiliary engines where the selected engine must match the thrust requirements at a certain speed. In Sinjai Regency, South Sulawesi, information was obtained related to the design of purse seine vessels, there are fish holds that are above the ship's deck. this was done because of the low draft of the ship, so that the impact on the resistance of the ship was not taken into account. This research will redesign the purse seine in Sinjai which has a hatch on the ship's deck without changing the shape of the bow and stern of the purse seine so that it has a better resistance value in two loading conditions, namely empty and fully loaded. The time and place of this research was carried out in January-June 2022 in Sinjai Regency. The sampling method used is a deliberate sampling method. The results showed that the total resistance of the ship was 44319.83 N with an engine power of 423430.25 W at maximum speed (13 knots). That it was concluded that the values before and after the redesign did not experience significant changes or the results obtained were the same as using the maxsurf resistance analysis, but for the samples after the redesign it was better because the hatch above the deck which took part of the area above the deck had been moved down to fill the void below the deck and provide ample space above the deck so that the crew can freely carry out their duties during fishing operations and also allow for a better stability value compared to the ship before the redesign.